2005
DOI: 10.1124/jpet.105.084210
|View full text |Cite
|
Sign up to set email alerts
|

Barakol Extracted from Cassia siamea Stimulates Chloride Secretion in Rat Colon

Abstract: Barakol is a purified extract of Cassia siamea, a plant that has been used as a laxative in traditional medicine. In this study, the effect of barakol on anion transport across the rat colon epithelium was investigated. Colonic epithelium was mounted in Ussing chambers and bathed with Ringer's solution. Addition of 1 mM barakol to the basolateral solution produced a slow increase in short-circuit current (Isc) in proximal colon and distal colon by 24.5 Ϯ 2.2 and 24.2 Ϯ 1.4 A/cm 2 , respectively. Barakol increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Most of the naturally laxative exert their effects on the colonic epithelium by stimulating Cl - secretion and/or inhibiting Na + absorption, resulting in an accumulation of fluid and subsequent increased colonic motility [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of the naturally laxative exert their effects on the colonic epithelium by stimulating Cl - secretion and/or inhibiting Na + absorption, resulting in an accumulation of fluid and subsequent increased colonic motility [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The functional segments demarcated by our study appear to have two easily identifiable anatomical features. First, the proximal portion of the colon that expresses abundant NHE3 but scant DRA (0 -20% length) roughly corresponds to the segment that displays serosal palmleaf striations (21,31,55). Second, the portion of the rodent distal colon that is deficient in NHE3 (60 -100% colon length in rats and 75-100% in mice) is largely comprised of the extraperitoneal segment that extends from the pelvic brim to the anus; previous studies have indicated that this segment, sometimes called the rectum (30), uniquely exhibits aldosterone-stimulated electrogenic Na ϩ absorption and a weaker Cl Ϫ secretory capacity (7,30,43).…”
Section: Discussionmentioning
confidence: 99%
“…Disorders resulting in increased Cl − secretion, for example in bacterial or viral infections, are a primary cause of secretory diarrhea (Field, 2003). Whereas, decreased secretory function or increased fluid absorption in the colonic epithelium is typically associated with cystic fibrosis and constipation (Deachapunya et al, 2005;Bijvelds et al, 2009).…”
Section: Introductionmentioning
confidence: 99%